Nutritional status and food intake are related to malnutrition risk and length of stay in hospitalized patients - Yalçın, Tuba; Yürük, Armağan Aytuğ; Türkoğlu, İnci and Ilgaz, Fatma and Açıkgöz, Aylin and Aksan, Ayşegül and Gökmen Özel, Hülya and Akal Yıldız, Emine and Samur, Gülhan (Progress in Nutrition, 2018)
Objective: The aim was to evaluate the relationship between food intake and malnutrition risk of hospitalized patients. Methods: In this study 192 hospitalized patients were included. Food intake was performed on 24 h recall dietary method Nutritional Risk Screening-2002 has been used to evaluate the nutritional status of patients. Odds ratios with 95% confidence intervals were computed using a univariate and multivariate stepwise logistic regression model with malnutrition risk as the response variable. Results: The mean age of individuals was 50.3±16.35 years, 29.4% of males and 20.0% of females were at risk group. The patients with malign neoplasms had the highest malnutrition risk score. The overall coverage of the energy, protein, fibre, vitamin C, vitamin B12, calcium, iron and the other micronutrients of the malnutrition risk group were significantly lower than well-nourished patients (p<0.05). This difference was more remarkable among the patients who were younger than 65 years. Recent weight loss increased the malnutrition risk, 1.1 times in the last three and 6 months (p=0.003), in the last two months 1.7 times (p=0.000) and in the last one month was 1.5 times (p=0.002). Conclusion: The factors associated with malnutrition can be identified as food intake, recent weight loss, length of stay and anthropometric measurements. Patients who were malnourished by screening tool presented decreased food intake and had longer length of stay. A comprehensive nutritional evaluation that will allow adequate intervention and nutritional therapy is needed to avoid hospital malnutrition.